Transparency Disparities in the Social Health Insurance System: The Rights of Social Security Agency Patients to Cost Details in the Indonesian Case-Based Groups System - Aida, Lutfi Nur; Suwandi, Nur Ainy Amira Puspitaning; Rato, Dominikus; Ohoiwatun, Y A Triana (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: There is an information disparity between Social Security Administration Agency patients and independent patient, where Social Security Administration Agency patients do not gget detail of service fees because the INA-CBG (Indonesia Case Based Groups) payment system is based on the diagnosis group, white independent patients get a complete cost receipt.Purposes of the Research: The Purpose of this study is to analyze the inequality of information transparency in the National Health Insurance system, especially related to the rights of Social Security Administration Agency patients to the details of service fees in the INA-CBG payment system. BPJS patients do not get details of costs like independent patients even though the use the same health facilities and evaluate the impact of the absence of such information on patients’ rights to transparency and accountability of health services.Methods of the Research: The research method used is normative juridical, namely legal research concucted by examiningliterature materials consisting of primary legal materials, secondary legal materials and tertiary legal material. This research uses a statute approach and an analyrical approach.Results Main Findings of the Research: The absence of detailed costs for Social Security Administration Agency patients has the pontential to violate the right to public information and consumer protection, which ultimately weekens the position of patients in objecting to the healt services received. This alsi reduces transparency and accountability in the implementation of the National Health Insurance, thereby hindering efforts to evaluate and improve the health service system for the community.